2015
DOI: 10.3390/ijerph120607059
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Community Treatment of an Inmate Population with Substance Use Disorders: Post-Release Trends in Re-Arrest, Re-Incarceration, and Drug Misuse Relapse

Abstract: This systematic literature review maps the evidence for the effectiveness of the therapeutic community interventions (TCI) in reducing re-arrest, re-incarceration or drug misuse following release from prison, including the extent to which these effects are retained over time. The databases searched for the review included PsychINFO, Medline and Scopus and reference lists from relevant articles published between 2007 and 2014. Only quantitative studies that examined the effectiveness of TCI for a prisoner popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 32 publications
0
23
3
1
Order By: Relevance
“…For instance, although treatment location effects were not the focus of this study, the present study found no differences in treatment effect for community-or prisonbased treatment, which departs from the results of previous studies that reported statistically significant differences between such treatment types (e.g., Galassi, Mpofu, & Athanasou, 2015;Hall, 1995b;Kim et al, 2016). The null effect of community-based treatments and prison-based treatments for reducing recidivism observed in this study may be explained by the fact that the current study sampled only 10 studies, which may have underpowered the analysis to detect differences that may in fact exist.…”
Section: Discussioncontrasting
confidence: 84%
“…For instance, although treatment location effects were not the focus of this study, the present study found no differences in treatment effect for community-or prisonbased treatment, which departs from the results of previous studies that reported statistically significant differences between such treatment types (e.g., Galassi, Mpofu, & Athanasou, 2015;Hall, 1995b;Kim et al, 2016). The null effect of community-based treatments and prison-based treatments for reducing recidivism observed in this study may be explained by the fact that the current study sampled only 10 studies, which may have underpowered the analysis to detect differences that may in fact exist.…”
Section: Discussioncontrasting
confidence: 84%
“…In addition, among stimulant users, a reverse tolerance from drugs has also been observed [20,21], in those with repeated use, psychopathic symptoms (e.g., auditory hallucinations and delusions) can develop from lower doses. Repeated stimulant use has been found to lead to poor physical health-related quality of life [22] and severe mental disorders [6,23,24,25]. To prevent repeated stimulant use, the perception of drug offenders toward drug dependence and treatment should be assessed in all prisons to illuminate the awareness of drug users.…”
Section: Discussionmentioning
confidence: 99%
“…The longer the history of stimulant use, the more difficult it is to overcome the drug addiction; thus, even if the prison sentence was longer, it is still difficult to completely withdraw from the drug. After being released from prison without sufficient treatment, it is more likely that such individuals would begin taking the drug again [24,28]. Therefore, the correctional and treatment programs in prison should administer treatment to addicted inmates in accordance with each individual’s level of awareness or motivation, in accordance with the health promotion theory [27,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutic communities are most effective in patients with polysubstance use disorders but fare poorly relative to OAT in patients with opioid use disorders [13]. In prison contexts, therapeutic communities show mixed results, with only short-term reductions in substance use and reincarceration, especially without a sustained aftercare program post-release [14]. Indeed, in a recent study of newly released prisoners with opioid use disorders in Malaysia, those who had received 24 months of therapeutic community support during detention were significantly less likely (10 vs 40%; p < 0.001) to have remained free from opioids within 12 months as compared to those who received voluntary methadone maintenance treatment [15].…”
Section: Introductionmentioning
confidence: 99%